2015
DOI: 10.1109/tnnls.2015.2388544
|View full text |Cite
|
Sign up to set email alerts
|

A Digital Liquid State Machine With Biologically Inspired Learning and Its Application to Speech Recognition

Abstract: This paper presents a bioinspired digital liquid-state machine (LSM) for low-power very-large-scale-integration (VLSI)-based machine learning applications. To the best of the authors' knowledge, this is the first work that employs a bioinspired spike-based learning algorithm for the LSM. With the proposed online learning, the LSM extracts information from input patterns on the fly without needing intermediate data storage as required in offline learning methods such as ridge regression. The proposed learning r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
115
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(115 citation statements)
references
References 45 publications
0
115
0
Order By: Relevance
“…The efficiency of the proposed architecture was demonstrated in a spike train classification task and an approximation task of retrieving the sum of firing rates of input spike trains. In another study, a biologically inspired local learning rule was presented for lowpower VLSI implementation of LSMs to reduce hardware implementation costs (Zhang et al, 2015). It was numerically shown that the overhead of hardware implementation can be reduced by the new learning rule in a speech recognition task.…”
Section: Vlsismentioning
confidence: 99%
“…The efficiency of the proposed architecture was demonstrated in a spike train classification task and an approximation task of retrieving the sum of firing rates of input spike trains. In another study, a biologically inspired local learning rule was presented for lowpower VLSI implementation of LSMs to reduce hardware implementation costs (Zhang et al, 2015). It was numerically shown that the overhead of hardware implementation can be reduced by the new learning rule in a speech recognition task.…”
Section: Vlsismentioning
confidence: 99%
“…System is trained and for 200 epochs on 500 TI-46 spoken digit samples. Performance is evaluated using 5 fold testing where accuracy is averaged over the last 20 epochs [15]. Samples used in training and testing consisted of a uniform distribution of 50 samples for each digit '0-9' and 100 samples for each speaker, among 5 female speakers.…”
Section: Performancementioning
confidence: 99%
“…LSMs have been successfully applied to several applications including speech recognition [10], vision [23], and cognitive neuroscience [11], [24]. Practical applications suffer from the fact that traditional LSMs take input in the form of spike trains.…”
Section: Liquid State Machinesmentioning
confidence: 99%
“…We build upon these efforts leveraging the benefits of low energy consumption, scalability, and run time speed ups and include an efficient implementation of arbitrarily complex synaptic response functions in a digital architecture. This is important as the synaptic response function has strong implications in spiking recurrent neural networks [10].…”
Section: Introductionmentioning
confidence: 99%